PENENTUAN STRUKTUR BAWAH PERMUKAAN DENGAN MENGGUNAKAN METODE SEISMIK REFRAKSI DI LAPANGAN PANAS BUMI DIWAK DAN DEREKAN, KECAMATAN BERGAS, KABUPATEN SEMARANG - Saiful Nurul Hudha; Udi Harmoko; Sugeng Widada; Yusuf D.H; Gatot Yulianto; Sahid Sahid (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
A research of refraction seismic methods in Diwak and Derekan village, Bergas district , Semarang regency , Central Java has been done on March 30, 2013 and August 27, 2013. This research in order to determination the subsurface structure of a geothermal field Diwak and Derekan with refraction method. In this aquisision data the travel time data was a distance function, with Geometrics Model ES-3000 seismic refraction instrument with 8 Geophones. Processing and interpretation data used Hagiwara method. Hagiwara method used value of delay time concept from travel time curve.This interpretation which resulted shows the subsurface lithology of the study area Diwak v1 obtained for the first layer of 297 – 412 m/s which we interpret as a layer of alluvium. While v2 on both layers obtained a value of 471 – 697 m/s which we interpret as soil. This research is the penetration depth of 5.84 - 11.7 m . The results obtained in the field structure of the two bedding Derekan, v1 to the first layer of 546 - 1011 m/s which is interpreted as alluvium. While v2 on both layers obtained a value of 1081 - 1714 m/s are interpreted with clay .Penetration that can be recorded on the field at 0.75 – 9.16 m .Keywords: sub surface structure, seismic refraction, Hagiwara method, Diwak, Derekan